Industrial training programme in the Department of Chemical Engineering, UTM: lessons learnt - Ahmad Zaini, Muhammad Abbas; Songip, Ahmad Rahman; Abdul Manan, Zainuddin; Kamarizan, Kidam (2006)
The undergraduate students at the Chemical Engineering Department at UTM are required to undergo industrial training programme at any related industries nationwide. There are several factors that need to be taken into account as students may face some difficulties during the training period. Behind the scene, the coordinator holds several important tasks that require full commitment and motivation to serve students. This paper describes the procedures and the lessons learnt from the early beginning students preparing to apply until the applications are approved as well as the coordinator’s roles and responsibilities to assist and provide good guidelines to ensure all students achieve the objectives of industrial training.